Lands of Azerbaijan According to Muslim Geographers Between the 9th-10th Centuries - Abdurahmanova, Saadat (Scholarya Demo Journal of Ruby, 2018)
The article aims to determine the borders of Azerbaijani lands through the study of Muslim geographers of the 9th-10th centuries. According to the sources concerning the topic, Islamic geographers divided the territory into three regions: Azerbaijan (includes the north and south parts of Azerbaijan), Arrân and Irminiya. However, some geographers mention only two territories, Azerbaijan and Irminiya. The same sources reveal that the most ancient Islamic geographers described the north of Azerbaian as Arran and the south of Azerbaijan as the current territory of Azerbaijan. Additionally, some geographers share valuable information about the borders and important cities of the mentioned territories. However, some geographers describe the borders differently and consider Arran and Azerbaijan as one territory. Nader Shah Afshar was the first person declaring the north and south of Azerbaijan as a single territory for the first time in the history. He abolished the province (beylerbeylik) of Tabriz, Chukur-Set Shirvan and Karabagh which covered northern and southern territories and united the region under the name of Azerbaijan. Thus, for the first time in the history, the southern and northern lands were declared together as Azerbaijan. With the establishment of the Azerbaijan Democratic Republic in 1918, the north lands of the Aras River started to officially be called Azerbaijan.